BUREAUCRATIC LANGUAGE AS A COMMUNICATIVE BARRIER IN STUDENTS’ ACADEMIC AND BUSINESS SPEECH - Ubozhenko A.S. (International Journal of Literature and Language Studies, 2026)
The article examines bureaucratic language as one of the common speech problems in students’ academic and business communication. The aim of the article is to describe the main manifestations of bureaucratic language in students’ academic and business speech and to propose a methodological model for overcoming it in Russian language and speech culture classes. The article identifies the main types of bureaucratization of speech: nominalization, redundancy, impersonality, cliché use, lack of addressivity and syntactic complication. A system of educational tasks aimed at recognizing, analysing and editing bureaucratic constructions is proposed. It is concluded that working with bureaucratic language contributes to the development of students’ communicative competence, clear writing skills and the quality of academic and business communication.